The Role of Parents in the Social Interaction of Deaf Children with their SMPLB Level Friends (Quantitative Descriptive Research at SLB in Lubuk Basung District) - Niken Desi Pranatalia; Damri Damri (Edumaspul: Jurnal Pendidikan, 2023)
Parents play a major role in aspects of a child's life. Parents also play an important role in the social interaction of children, especially deaf children. But in reality there are children who have difficulty controlling their emotions in interacting with peers and some are also lacking in terms of interaction and are limited during interactions. This is where the important role of parents of deaf children is needed. This study aims to determine the role of parents in the social interaction of deaf children with their peers at the SMPLB level at SLB Negeri 1 Lubuk Basung and SLB Batu Kambing. The method in this study was descriptive quantitative with a sample of twenty parents of deaf children. The data that the researchers used in this study was in the form of a questionnaire which was distributed to deaf parent respondents. This study uses data analysis techniques in the form of percentages with the given categories, namely very good, good, fair and not good categories. The results of this study can be concluded that the role of parents of deaf children in social interaction is divided into four, namely; aspects of parents as caregivers with a percentage of 25.5%, aspects of parents as educators with a percentage of 33%, parents as mentors with a percentage of 35.83%, and aspects of parents as motivation with a percentage of 29 .5%, the the sum of the four indicators can be accumulated with a percentage of 16.43%, indicating the results of the category are not good. The results of this study can be concluded that the role of parents of deaf children in social interaction is divided into four, namely; aspects of parents as caregivers with a percentage of 25.5%, aspects of parents as educators with a percentage of 33%, parents as mentors with a percentage of 35.83%, and aspects of parents as motivation with a percentage of 29 .5%, the the sum of the four indicators can be accumulated with a percentage of 16.43%, indicating the results of the category are not good. The results of this study can be concluded that the role of parents of deaf children in social interaction is divided into four, namely; aspects of parents as caregivers with a percentage of 25.5%, aspects of parents as educators with a percentage of 33%, parents as mentors with a percentage of 35.83%, and aspects of parents as motivation with a percentage of 29 .5%, the the sum of the four indicators can be accumulated with a percentage of 16.43%, indicating the results of the category are not good.